The multicultural riddle : rethinking national, ethnic, and religious identities - Baumann, Gerd. (New York : Routledge, 1999)
A comprehensive exploration of all the issues that shape our search for a multicultural society.
Book Cover; Title; Contents; About This Book; ~I Have a Dream~; but Who Is It For?Civil Rights, Human Rights, or Community Rights?; From Dreaming to Meaning: The Multicultural Triangle National Culture, Ethnic Culture, Religion as Culture; The Nation-State, I: Postethnic or Pseudotribe? Why Nation-States Are Not Ethnically Neutral; The Nation-State, II: Business or Temple? Why Nation-States Are Not Religiously Neutral; Ethnicity: Blood or Wine? Not Biological Essence, but Cultivated Ferment; Religion: Baggage or Sextant? Not Immutable Heritage, but Positioning in Context.
Includes bibliographical references (pages 159-172) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Ethnicity; Multiculturalism; Human rights; Civil rights; Religion and culture; Human Rights; Civil Rights; Ethnicité.; Multiculturalisme; Droits économiques et sociaux; Droits de l'homme.; Religion et culture; Droits de l'homme (Droit international); ethnicity; multiculturalism; civil rights; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Civil rights; Ethnicity; Human rights; Multiculturalism; Religion and culture; Etnische identiteit; Godsdienst; Multiculturele samenlevingen